## Calculus with Applications (10th Edition)

$$y = - 2 + 22{e^{{x^2} - 1}}$$
\eqalign{ & \frac{{dy}}{{dx}} - 2xy - 4x = 0,\,\,\,\,\,\,\,\,\,\,\,y\left( 1 \right) = 20 \cr & {\text{adding }}4x{\text{ to both sides}} \cr & \frac{{dy}}{{dx}} - 2xy = 4x \cr & {\text{this equation is already written in the form }}\frac{{dy}}{{dx}} + P\left( x \right)y = Q\left( x \right) \cr & {\text{comparing }}\frac{{dy}}{{dx}} - 2xy = 4x{\text{ with }}\frac{{dy}}{{dx}} + P\left( x \right)y = Q\left( x \right){\text{ we can note that }}P\left( x \right){\text{ is }} - {\text{2x }} \cr & {\text{The integrating factor is }}I\left( x \right) = {e^{\int {P\left( x \right)} dx}} \cr & I\left( x \right) = {e^{\int {P\left( x \right)} dx}} = {e^{\int { - 2xdx} }} = {e^{ - {x^2}}} \cr & {\text{multiplying both sides of the differential equation by }}{e^x} \cr & {e^{ - {x^2}}}\frac{{dy}}{{dx}} - 2xy{e^{ - {x^2}}} = 4x{e^{ - {x^2}}} \cr & {\text{Write the terms on the left in the form }}{D_x}\left[ {I\left( x \right)y} \right] \cr & {D_x}\left[ {{e^{ - {x^2}}}y} \right] = 4x{e^{ - {x^2}}} \cr & {\text{solve for }}y{\text{ integrating both sides}} \cr & {e^{ - {x^2}}}y = \int {4x{e^{ - {x^2}}}} dx \cr & {e^{ - {x^2}}}y = - 2\int {{e^{ - {x^2}}}\left( { - 2x} \right)} dx \cr & {e^{ - {x^2}}}y = - 2{e^{ - {x^2}}} + C \cr & y = - 2 + \frac{C}{{{e^{ - {x^2}}}}} \cr & y = - 2 + C{e^{{x^2}}}\,\,\,\,\left( {\bf{1}} \right) \cr & {\text{we can find the constant }}C{\text{ using the initial value problem}}\,\,\,y\left( 1 \right) = 20 \cr & {\text{substituting these values into }}\left( {\bf{1}} \right) \cr & 20 = - 2 + C{e^{{{\left( 1 \right)}^2}}} \cr & 20 = - 2 + Ce \cr & C = \frac{{22}}{e} \cr & {\text{substitute }}C = \frac{{22}}{e}{\text{ into }}\left( {\bf{1}} \right){\text{ to find the particular solution}} \cr & y = - 2 + \frac{{22}}{e}{e^{{x^2}}} \cr & y = - 2 + 22{e^{{x^2} - 1}} \cr}